Peranan Klaim Gizi dan Kesehatan pada Susu Pertumbuhan sebagai Penentu Keputusan Pembelian - Ayu Puspitalena RTR; Nurheni Sri Palupi; Puspo Edi Giriwono (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
This moment, it has not been known the role of nutrition and health claims as purchasing decision determination. Objective of the research is to study the role of nutrition and health claims on the labels of growing up milk as purchasing decision and to analyze corellation of respondent's characteristics which have influence. Study was conducted by survey, data were analyzed descriptively and statistically. Label of growing up milk for children 1-3 years old read by 70% respondent and 30% occasionally, and 23% of respondents do not read nutrition and health claims. Nutritional and health claims have a role as a determinant of purchasing decisions for consumers of 24%. As for the 76% purchase decision is influenced by other factors such as suitable with a child, nutrient content, good taste or price. The role of nutritional and health claims as a determinant of purchase decisions are influenced by factors of education, family expenses per month and expenditure for milk per month. As for the other factors that include age, occupation, number of children, place of purchase, and frequency of purchases did not affect the role of nutrition and health claims as a determinant of purchase.